2010
DOI: 10.1161/circresaha.109.211797
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin

Abstract: Key Words: diabetes Ⅲ myocardial infarction Ⅲ adipocytokine Ⅲ signaling D iabetes mellitus and its resultant cardiovascular disease are a dominant public health problem. The hyperglycemia and hyperlipidemia associated with diabetes mellitus not only result in vascular injury causing greater myocardial infarction (MI) morbidity but also directly impact ischemic cardiomyocytes adversely, causing larger infarct size 1,2 and more severe heart failure 3 after MI, further contributing to higher mortality. Effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…46 Interestingly, CTRP9 forms heterotrimers with APN, and appears to share the AdipoR1 in both cultured endothelial cells and cardio- ide production, culminating in unfavorable cardiovascular outcomes. 80 In a recent study investigating the direct mechanisms underlying both APN signaling and APN resistance, GRK2 phosphorylated APN receptor 1 post-MI impaired the cardioprotective functions of APN. 81 Inhibition of GRK2-mediated AdipoR1 phosphorylation represents a completely novel manner of restoring APN cardioprotective signaling in the post-MI injury period.…”
Section: Ctrp9mentioning
confidence: 99%
“…46 Interestingly, CTRP9 forms heterotrimers with APN, and appears to share the AdipoR1 in both cultured endothelial cells and cardio- ide production, culminating in unfavorable cardiovascular outcomes. 80 In a recent study investigating the direct mechanisms underlying both APN signaling and APN resistance, GRK2 phosphorylated APN receptor 1 post-MI impaired the cardioprotective functions of APN. 81 Inhibition of GRK2-mediated AdipoR1 phosphorylation represents a completely novel manner of restoring APN cardioprotective signaling in the post-MI injury period.…”
Section: Ctrp9mentioning
confidence: 99%
“…Clinically, circulating adiponectin levels are reduced in patients with obesity-linked complications, including type 2 diabetes and peripheral arterial occlusive disease (12,13,24). Thus, therapeutic approaches aimed at increasing adiponectin could be useful for treatment of cardiovascular disease (18,38).…”
mentioning
confidence: 99%
“…Infarct sizes in PRIT subgroups were significant smaller than those in the control MI subgroups, and this post-MI reduction in infarct size was time dependent (Figure 4). Sudden occlusion of a major coronary artery can result in AMI and rapid apoptosis of cardiomyocytes, leading to progressive fibrous replacement in the myocardium and LV dilatation [3,25]. Previous studies [26][27][28] demonstrated that physiologic RIT could promote coronary collateral formation in the ischemic myocardium.…”
Section: Discussionmentioning
confidence: 99%